2022
DOI: 10.1007/s11682-022-00638-5
|View full text |Cite
|
Sign up to set email alerts
|

The fMRI correlates of visuo-spatial abilities: sex differences and gender dysphoria

Abstract: The contribution of brain regions to visuospatial abilities according to sex differences and gender identity is inconsistently described. One potential explaining factor may be the different tasks employed requiring a variable load of working memory and other cognitive resources. Here we asked to 20 cis and 20 transgender participants to undergo functional Magnetic Resonance Imaging during performance of a judgement line of orientation test that was adapted to explore the basic visuospatial processing while mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…What is truly interesting, however, is what happens in the HDMS condition, in which women's performance increases in accuracy compared to the PC condition. Regardless of performance, several behavioral and neuroimaging studies have highlighted that women tend to rely more than men on working memory and cognitive control processes to perform visuospatial tasks [64][65][66][67][68]. This evidence suggests a compelling intersection between cognitive processes and gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…What is truly interesting, however, is what happens in the HDMS condition, in which women's performance increases in accuracy compared to the PC condition. Regardless of performance, several behavioral and neuroimaging studies have highlighted that women tend to rely more than men on working memory and cognitive control processes to perform visuospatial tasks [64][65][66][67][68]. This evidence suggests a compelling intersection between cognitive processes and gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, anomic aphasia has been categorized as a logopenic symptom of Alzheimer's disease with regards to language. Recent research by Gavazzi et al [19] has shown that within efficient encoding of novel objects, there is desynchronization between networks that are involved in language and visuo-spatial abilities. Conversely, synchronization between these networks hinders successful semantic encoding.…”
Section: Human Self-awarenessmentioning
confidence: 99%